Solvent-Directed Transformation of the Self-assembly and Optical Property of a Peptide-Appended Core-Substituted Naphthelenediimide and Selective Detection of Nitrite Ions in an Aqueous Medium - Gayen, Kousik (Langmuir : the ACS journal of surfaces and colloids, 2021)
This study vividly displays the different self-assembling behavior and consequent tuning of the fluorescence property of a peptide-appended core-substituted naphthalenediimide (N1) in the aliphatic hydrocarbon solvents (n-hexane/n-decane/methyl cyclohexane) and in an aqueous medium within micelles. The N1 is highly fluorescent in the monomeric state and self-aggregates in a hydrocarbon solvent, exhibiting "H-type" or "face-to-face" stacking as indicated by a blue shift of absorption maxima in the UV-vis spectrum. In the H-aggregated state, the fluorescence emission of N1 changes to green from the yellow emission obtained in the monomeric state. In the presence of a micelle-forming surfactant, cetyl trimethylammonium bromide (CTAB), the N1 is found to be dispersed in a water medium. Interestingly, upon encapsulation of N1 into the micelle, the molecule alters its self-assembling pattern and optical property compared to its behavior in the hydrocarbon solvent. The N1 exhibits "edge-to-edge" stacking or J aggregates inside the micelle as indicated by the UV-vis spectroscopic study, which shows a red shift of the absorption maxima compared to that in the monomeric state. The fluorescence emission also differs in the water medium with the NDI derivative exhibiting red emission. FT-IR studies reveal that all amide NHs of N1 are hydrogen-bonded within the micelle (in the J-aggregated state), whereas both non-bonding and hydrogen-bonding amide NHs are present in the H-aggregated state. This is a wonderful example of solvent-mediated transformation of the aggregation pattern (from H to J) and solvatochromism of emission over a wide range from green in the H-aggregated state to yellow in the monomeric state and orangish-red in the J-aggregated state. Moreover, the J aggregate has been successfully utilized for selective and sensitive detection of nitrite ions in water even in the presence of other common anions (NO3-, SO42-, HSO4-, CO32-, and Cl-)